GAS PRODUCTION AND UTILIZATION IN NIGERIA: A LONG-TERM PERSPECTIVE - Biose, Henry (International Journal of Engineering Technologies and Management Research, 2019)
The study reviewed the gas production and utilization in Nigeria and outlines strategies for long term development. There is weak gas resource management system in Nigerian that has resulted to gas production being at 8.0bscf/d with utilization of 39% (2.9 bscf/d) on NLNG, 31% (2.3 bscf/d) on reinjection and other operational usage, 15% (1.1 bscf/d) on gas flaring and 16% (1.2bscf/d) on domestic gas consumption. The study shows a 41% daily average domestic gas supply obligation performance. Extensive review of related literatures was used to obtain relevant data and information on gas production and utilization in Nigeria. The study revealed inconsistencies and low gas production and utilization in Nigeria with respect to the Nigerian Gas Master plan that was not fully implemented, relatively low gas flare penalty and insufficient domestic gas utilization projects. The compressed natural gas utilization in Nigeria has only been used in Benin-City for cars, Nestle Shagamu factory and Power gas Africa. The proposed strategy for the long-term gas production and utilization in Nigeria includes sustainable management structure, sustainable governance and regulatory structure and sustainable financing structure.